Kebijakan Publik Dalam Pengembangan Sumber Daya Panas Bumi Sebagai Upaya Mengatasi Krisis Energi Nasional dan Meningkatkan Sumber Penerimaan Keuangan Daerah - Tasrin, Krismayati (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2006)
Geothermal is one of the energy source than can be used as good alternative energy, because it is a renewable energy source. Long-used fossil fuel (oil and coal) as main source of energy are non renewable, while there are limited sources that will be depleted in a couple years. In addition, geothermal energy is an environmental friendly, and abundant and widespread in our country, while the use of it in electricity generation is still rarely applied except in West Java. Therefore geothermal is not only provide answer to the national energy crisis but also increase the revenue source of local governments in region where there are geothermal potentials exist and developed. To use the geothernal energy, it needs government commitment to attract the investors to put their investment and to make public policies that support a good business condition.